Logistical Component of Sustainable Development of Regions in the Context of Decentralization Processes: Ukrainian Case. - Korbutiak, Alina; Yudenko, Ye; Onyshchenko, O (Instituto Federal de Educação, Ciência e Tecnologia de São Paulo, 2020)
The aim of the study is to reveal the logistical component of sustainable development of regions in the context of decentralization reform in Ukraine. The role of logistics in ensuring the balanced development of regions and united territorial communities to gain their competitive advantages is shown. The dynamics of the Logistics Efficiency Index (LEI) of Ukraine in comparison with some other countries and the dynamics of the components of LPI in Ukraine for the period 2007-2018 are analysed. A number of problems that cause a low level of logistics in Ukraine have been identified and ways to improve the logistics activities of the regions have been proposed. A system for managing the logistics activities of the united territorial communities has been developed, which is the starting point for the organization of the social development management system. The system is a multi-component structure that combines objects, tasks, management methods and techniques, evaluation indicators and indicators. It should cover enterprises of production and non-production spheres, infrastructure facilities, organizations and institutions, interconnected in the decision-making process on the directions and ways of using elements of resource flow in the region and aimed at through optimization of flow processes based on estimating and minimizing logistics costs.
Keywords: Decentralization United territorial communities Region Sustainable development Logistics